2017
DOI: 10.1093/mnras/stx2845
|View full text |Cite
|
Sign up to set email alerts
|

ALMA + VLT observations of a damped Lyman-α absorbing galaxy: massive, wide CO emission, gas-rich but with very low SFR

Abstract: We are undertaking an ALMA survey of molecular gas in galaxies selected for their strong HI absorption, so-called DLA/sub-DLA galaxies. Here we report CO(2-1) detection from a DLA galaxy at z = 0.716. We also present optical and near-infrared spectra of the galaxy revealing [OII], Hα and [NII] emission lines shifted by ∼ 170 km s −1 relative to the DLA, and providing an oxygen abundance 3.2 times solar, similar to the absorption metallicity. We report low unobscured SFR∼ 1 M ⊙ yr −1 given the large reservoir o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 125 publications
4
40
0
Order By: Relevance
“…The spectrum shows that the CO emission is redshifted from the centroid of the DLA at z = 2.5832 by 131 km s −1 . There is marginal evidence for a "boxy" or double-horned line profile (Davis et al 2011), similar to the CO(2−1) and CO(1−0) line profiles observed for two other, low-z absorbing galaxies (Neeleman et al 2016;Møller et al 2018). This indicates that this galaxy has some degree of a rotational support and/or emission from several sub-clumps.…”
Section: Co Emission and Molecular Gas Massmentioning
confidence: 58%
See 1 more Smart Citation
“…The spectrum shows that the CO emission is redshifted from the centroid of the DLA at z = 2.5832 by 131 km s −1 . There is marginal evidence for a "boxy" or double-horned line profile (Davis et al 2011), similar to the CO(2−1) and CO(1−0) line profiles observed for two other, low-z absorbing galaxies (Neeleman et al 2016;Møller et al 2018). This indicates that this galaxy has some degree of a rotational support and/or emission from several sub-clumps.…”
Section: Co Emission and Molecular Gas Massmentioning
confidence: 58%
“…The first pilot studies of DLAs with ALMA have given quite interesting results. Møller et al (2018) studied a single system at z = 0.716 and found a surprisingly large molecular mass and for that mass surprisingly low star-formation rate placing the object away from the normal galactic scaling relations for these quantities. Kanekar et al (2018) studied a sample of DLAs at similar redshifts and found a surprisingly large detection rate of CO-emission from the galaxy counterparts of the absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the optical searches such as the one described here, there are on-going campaigns detecting with ALMA molecular emission lines from absorption selected galaxies (Neeleman et al 2016(Neeleman et al , 2018Klitsch et al 2018;Møller et al 2018;Kanekar et al 2018). Combining optical and sub-mm wavelengths observations of absorber host galaxies will bring new insights into the role of molecular gas in the CGM of galaxies.…”
Section: Resultsmentioning
confidence: 96%
“…These molecular masses are large in comparison with the typical stellar mass of absorbing galaxies . In fact, a number of recent works have reported CO associated with quasar absorbers from ALMA observations with a high rate of incidence and derived equally high molecular masses (Neeleman et al 2016;Møller et al 2018;Neeleman et al 2018;Kanekar et al 2018;Klitsch et al 2018;D'Odorico et al 2018;Klitsch et al 2019). However, it is unclear why H i-rich absorbing galaxies should have large reservoir of H2 gas.…”
Section: Physical Properties Of the Galaxy Groupmentioning
confidence: 99%